IMPLEMENTASI PENDEKATAN SUPERVISI PEMBELAJARAN DIREKTIF DALAM MENINGKATKAN PROFESIONALISME GURU DI MI/SD - Zuhriyah, Indah Aminatuz (Madrasah: Jurnal Pendidikan dan Pembelajaran Dasar, 2010)
Supervised learning approach directive is part of the supervision of development (developmental supervision). This approach is based on the fact, that basically the process of supervision is a learning process where the supervision took the role of teacher, in the sense of supervisors berperana as teachers, and teachers as students of a learning relationship to other learning. The bottom line is that this approach should examine important elements in the next stage of development of teachers to use in establishing a relationship and approach to supervision, where supervisors work together with teachers. This is done, because of differences in the characteristics of the study (teacher). The differences of these characteristics is closely related to two important elements of the effectiveness of teacher professionalism in performing their duties, namely the commitment and ability to think abstraks. Supervision of this developmental approach do not see each approach (directive, collaborative, and non-directive) as a stand-alone approach and-separated, but rather something that is intact in a continuum. Supervision was developed from the directive so as to achieve nondirektif and simultaneously also membelajarkan teachers.